MAKING SPACE FOR WOMEN’S HISTORY: RHETORIC, DIGITAL ACTIVISM AND THE NATIONAL WOMEN’S HISTORY (CYBER)MUSEUM - Chabot, Shersta (AoIR Selected Papers of Internet Research, 2015)
This paper investigates the rhetorical processes through which feminist activists in the United States “make space” for their work via digital media technologies. Using the National Women’s History (Cyber)Museum (NWHM) as a focus, this paper explores the significant shifts that history museums in the United States have recently undergone within the cultural imaginary, shifts necessitated by a booming digital entertainment industry, social media and mobile devices. Museums have long held a venerated place in U.S. culture – we look to our history museums to provide us with information about the past, connecting us to carefully curated ideological and cultural narratives that live on in the public memory as artefacts live on in museum displays (Hooper-Greenhill, 2000). In this sense, the history museum engages in a critical form of rhetorical agency, one that contributes to and shapes public memory in very specific ways (Blair, 1999). But does this agency also shift as the history museum shifts from physical form to digital form, or vice versa? Can a “cyber” museum like the NWHM perform the same rhetorical work accomplished by more traditional history museums? Such questions hold critical implications for current and future museum projects that seek to address—and correct-- longstanding national historical narratives that obscure, stereotype or erase the contributions of women and people of color from an otherwise collective past.